Analysis of Arsenic and Chromium Content and Pollution Index in Rice Fields in Tempuran Subdistrict, Karawang Regency - Zhafira Izzatul Mila; Gina Lova Sari; Ing. Willma Nurrul Adzillah (Jurnal Biologi Tropis, 2026)
Heavy metals are one of the most dangerous pollutants because they are non-degradable. This study aims to analyze the content of arsenic (As) and chromium (Cr) and evaluate the level of pollution in rice field soil in Tempuran Subdistrict, Karawang Regency. Soil samples were taken in 14 villages, with 10 points taken in each village using purposive sampling. Laboratory analysis was conducted to determine the As and Cr content in the rice field soil, and then calculate the heavy metal pollution index value. The results of this study show that the concentration of As, a heavy metal, is still below the quality standard, while Cr varies in each village. Based on the calculation of the pollution index using the Contamination Factor (Cf), Pollution Load Index (PLI), Ecological Risk Index (Re), Ecological Risk Potential Index (RI), and Geoaccumulation Index (Igeo), it was found that the rice fields in Tempuran Subdistrict were categorized as unpolluted to polluted in several villages. The results of mapping with ArcGIS to determine the distribution of heavy metals show that the Ar levels in all research locations are relatively uniform and are displayed in green, indicating that the values are below the quality standards. In contrast, chromium is displayed in shades of light brown to dark brown, reflecting variations in levels in each village, where some areas are below the quality standards, and others exceed the specified thresholds.